2023
DOI: 10.3390/healthcare11091355
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Acupuncture on Health-Related Quality of Life in Patients Receiving Maintenance Hemodialysis

Abstract: Patients with kidney failure (KF) receiving maintenance hemodialysis (HD) experience numerous symptoms that impair their health-related quality of life (HRQOL) and contribute to high mortality rates. Acupuncture is often used for symptom enhancement and HRQOL. This blinded, randomized, controlled patient-assessor trial evaluated the effectiveness of acupuncture compared with sham acupuncture on patients’ HRQOL receiving maintenance HD as a secondary analysis. Seventy-two participants were randomly assigned to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 58 publications
1
5
0
Order By: Relevance
“…Similarly, another study was conducted by Bullen et al [18] on 101 patients with end-stage renal disease, but this time acupuncture was associated with a massage procedure. The conclusion of this study was an improvement in the overall healthrelated quality of life of the 101 patients, which is confirmed by a new study that revealed that acupuncture was found to enhance the health-related quality of life in individuals undergoing maintenance hemodialysis following their treatment [19]. In addition, a study by Tsai et al [20] focused on the impact of acupuncture on the reduction of restless leg syndrome (RLS) in hemodialysis patients.…”
Section: Acupuncturesupporting
confidence: 62%
See 1 more Smart Citation
“…Similarly, another study was conducted by Bullen et al [18] on 101 patients with end-stage renal disease, but this time acupuncture was associated with a massage procedure. The conclusion of this study was an improvement in the overall healthrelated quality of life of the 101 patients, which is confirmed by a new study that revealed that acupuncture was found to enhance the health-related quality of life in individuals undergoing maintenance hemodialysis following their treatment [19]. In addition, a study by Tsai et al [20] focused on the impact of acupuncture on the reduction of restless leg syndrome (RLS) in hemodialysis patients.…”
Section: Acupuncturesupporting
confidence: 62%
“…Five principal strategies were identified. Among these, acupuncture demonstrated considerable promise as a benign and efficacious supplementary therapy for managing pain, enhancing functional capacity and muscular strength, lessening symptoms of restless leg syndrome and uremic pruritus, and bettering the QOL of patients on hemodialysis [ 13 , 19 ]. Nonetheless, additional investigations are imperative to confirm these results and define the ideal parameters for treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the small amount of data and high risk of bias for other symptomatic outcomes make it impossible to draw definitive conclusions. Three studies reported positive results of acupuncture therapy for quality of life [ 34 , 48 , 52 ], which may be related to the prognosis of acupuncture for relief of CKD-related symptoms; after all, symptom distress is strongly and negatively associated with quality of life in CKD patients [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…The effectiveness of acupuncture was assessed by scrutinizing the overall results described in a previous RCT [20,21]. The group that received verum acupuncture (VA) demonstrated better results, compared to the group that received sham (SA) acupuncture and a control group.…”
Section: Effectivenessmentioning
confidence: 99%
“…Our prior studies evaluated the impacts of acupuncture on the functional capacity (FC) and health-related quality of life (HRQOL) of patients undergoing hemodialysis (HD), pointing to the possibility of integrating this practice during HD sessions [20,21]. Given the promising results obtained and the limited number of national studies in this field, this paper aims to assess the opinions and perceptions of patients and health professionals regarding the acceptance of incorporating acupuncture as an integrative approach in the context of a Portuguese health services and conventional medicine.…”
Section: Introductionmentioning
confidence: 99%